PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN IPAS KELAS VI DI SDN 104205 TEMBUNG T.A 2025/2026 - Feby Nisha Bintang; Eva Betty Simanjuntak; Laurensia Perangin-angin; Lala Jelita Ananda; Imelda Free Unita (Universitas Negeri Medan, 2026)
This study aimed to develop a Problem Based Learning (PBL)-based Student Worksheet (LKPD) for Grade VI Science and Social Studies (IPAS) learning on the topic of Energy and Its Utilization at SDN 104205 Tembung and to determine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of the study were 20 Grade VI students. Data were collected through material expert validation sheets, design expert validation sheets, student response questionnaires, and pretest-posttest instruments. The results showed that the developed LKPD achieved a validity score of 90% from material experts, indicating a valid category. The practicality assessment based on student responses reached more than 90%, categorized as very practical. The effectiveness test using the N-Gain formula showed an increase in learning outcomes, with the average pretest score of 61.60 and posttest score of 84.43, resulting in an N-Gain value of 0.594 in the medium category. These findings indicate that the developed PBL-based LKPD is valid, practical, and sufficiently effective for IPAS learning while supporting the development of students’ 4C skills (critical thinking, creativity, collaboration, and communication).